Theoretical and Methodological Principles of Investment Support for Innovation-Oriented Development of Agrarian Production - ZORIA, Oleksii; YASNOLOB, Ilona; GALYCH, Oleksandr; CHERCHATYI, Oleksandr; TIUTIUNNYK, Yurii; TIUTIUNNYK, Svitlana; DUGAR, Tetiana; KALIAN, Oleksandr; MOKIIENKO, Tetyana (Journal of Environmental Management and Tourism, 2022)
The theoretical and methodological foundations of investment support for innovation-oriented development of the agrarian production were worked out and substantiated in the article. The systematization of theoretical approaches was conducted and the peculiarities of innovation development investment support of the agrarian production in modern conditions were determined. The factors affecting the process of investment support of the agrarian production innovation development were determined. The substantiation of the factors that form the innovative activity of the agrarian production and the process of its investment provision were conducted. The principles of investment support of the agrarian production innovation-oriented development were supplemented, to which the principle of balanced development was added. The essence of this principle is the parallel implementation of investment and innovative activities. Considering this principle makes it possible to pursue investment policy in the agrarian sector in terms of activating investment advantages and continuous mastering of new knowledge and innovations, taking into account branch and regional peculiarities. The concept was developed as to creating the economic mechanism of regulating the investment support of the agrarian production innovation development which depends on the chosen purposes of the branch development and influence of external and internal environmental factors on investment, and the conditions of its innovative potential development, revealing the main factors, favoring or preventing from activating the investment activities in the agrarian sector and act on the object of management. Implementation of the economic regulation mechanism allows to provide the procedure of the organizing efficiency management and to form methodological tools, measuring it depending on the type of developing investment and innovative processes in the agrarian sphere.